A superação do solipsismo a partir da 5ª meditação cartesiana: uma interpretação ética - Moor, Rudinei Cogo (2012)
The present work aims to elaborate on solipsism how philosophical problem and attempt to overcome as from the Husserlian phenomenology. We leave the analysis of the concept of solipsism and then describe the place that it occupies in the philosophies of Augustine, Descartes and Husserl. Then will deal about intersubjectivity in Husserl as an attempt to overcome. We stress the importance of the discussion that Husserl gives the question the other and, therefore, to examine thinkers Merleau-Ponty, Levinas and Waldenfels overcoming ethical solipsism. In order to achieve such objective, we will make a reconstructive and immanent analysis, divided into three parts, of the aspects relevant to this issue, as well as some of the critical readings available. First we show the Husserl s philosophical trajectory, the basic aspects of its phenomenology regarding the question of solipsism and is carried out as an attempt to overcome through intersubjectivity. Thus, at first we will try to thematize the concept of solipsism in general, passing by the subjectivist philosophies of nature as Augustine and Descartes. Following the central concepts of phenomenology will be analyzed, as well as the distance a head of the philosophical tradition and its possible response to solipsism. Finally, we analyze how proposal from the Husserlian intersubjectivity, is forwarded to the question of intersubjectivity in the philosophies of Merleau-ponty, Levinas and Bernhard Waldenfels to overcome charges of solipsistic and put the ethical treatment required with respect to others.